2002
DOI: 10.1007/s11661-002-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Subgrain formation during deformation: Physical origin and consequences

Abstract: The formation of subgrains in the course of plastic deformation is explained as a result of a trend to make the deformation easier by locally reducing the number of active slip systems. Local preference of one slip system changes the crystal orientation with respect to stress (Schmid factor), thus leading to geometrical softening or hardening. The trend to subgrain formation is treated in the framework of continuum mechanics as an instability against internal bending for the simple case of a crystal originally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…The subgrains stem from a patterning process leading (4) the power-law breakdown is too sharp so that an to the grouping of dislocations into a dislocation-poor cell extended region with an average stress exponent 5 of interior and dislocation-rich cell boundaries. [48,49] As the cell the steady-state creep rate is missing.…”
Section: B Solid Solutionsmentioning
confidence: 99%
“…The subgrains stem from a patterning process leading (4) the power-law breakdown is too sharp so that an to the grouping of dislocations into a dislocation-poor cell extended region with an average stress exponent 5 of interior and dislocation-rich cell boundaries. [48,49] As the cell the steady-state creep rate is missing.…”
Section: B Solid Solutionsmentioning
confidence: 99%
“…Dislocations accompanied by instantaneous strain directly after loading or dislocations introduced before loading by martensitic transformation or cold working are annihilated or redistributed repeatedly, reducing the total elastic energy and gradually forming a cell structure or sub-grains during transition creep of polycrystalline metals, which is followed by steady-state creep (Hasegawa, Karashima, & Hasegawa, 1971;Takeuchi & Argon, 1976;Spigrarelli, 1995a and1995b;Sawada, Maruyama, Komine, & Nagae, 1997;Sedlacek, Blum, Kratochvil, & Forest, 2002;Kratochvil & Sedlacek, 2004). For many types of metals, it has been confirmed that the observed average size of the sub-grains ( ) in steady-state creep can be formulated from the applied stress, , using an exponential law (Mukherjee, 1975;Takeuchi & Argon, 1976;Kassner, 2009) = , (1) where and are constants.…”
Section: Introductionmentioning
confidence: 99%
“…5b show very similar microstructures, with similar low-angle-boundary ratios. The difference in mechanical properties after annealing is caused by the difference in position of the sub-grain boundaries formed in cold rolling [14]. Specimen A2 forms sub-grain boundaries inside the small grains produced by hot rolling, while A3 forms large grains by dynamic recrystallization during hot rolling.…”
Section: Strength Change After Different Processing Stepmentioning
confidence: 99%